2014
DOI: 10.1001/jamapsychiatry.2014.62
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intravenous Ketamine for Treatment of Chronic Posttraumatic Stress Disorder

Abstract: IMPORTANCE Few pharmacotherapies have demonstrated sufficient efficacy in the treatment of posttraumatic stress disorder (PTSD), a chronic and disabling condition.OBJECTIVE To test the efficacy and safety of a single intravenous subanesthetic dose of ketamine for the treatment of PTSD and associated depressive symptoms in patients with chronic PTSD. DESIGN, SETTING, AND PARTICIPANTS Proof-of-concept, randomized, double-blind, crossover trial comparing ketamine with an active placebo control, midazolam, conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
362
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(376 citation statements)
references
References 33 publications
7
362
0
7
Order By: Relevance
“…Antidepressant doses of ketamine decreased the default mode connectivity (Scheidegger et al, 2012) and reduced core symptoms of PTSD, including avoidance (Feder et al, 2014). Based on these observations in humans and our findings in mice, we hypothesize that silent synapses underlie the enhanced functional connectivity in mental disease, whereas positive effects of ketamine result from their elimination.…”
Section: Ketamine Against Psychological Traumasupporting
confidence: 64%
“…Antidepressant doses of ketamine decreased the default mode connectivity (Scheidegger et al, 2012) and reduced core symptoms of PTSD, including avoidance (Feder et al, 2014). Based on these observations in humans and our findings in mice, we hypothesize that silent synapses underlie the enhanced functional connectivity in mental disease, whereas positive effects of ketamine result from their elimination.…”
Section: Ketamine Against Psychological Traumasupporting
confidence: 64%
“…Glutamate is thought to play a key role in the pathogenesis of PTSD (5, 6) for several reasons: glutamate underlies synaptic plasticity and memory formation (7), stress significantly impacts glutamate transmission (8), and the glutamate receptor antagonist ketamine may have efficacy in treating PTSD (9). Metabotropic glutamate receptors (mGluRs) are G protein-coupled receptors that mediate neuromodulatory effects of glutamate, making them a promising target for drug development (10).…”
mentioning
confidence: 99%
“…We recently reported that ketamine was superior to an anesthetic control condition (the benzodiazepine midazolam) at rapidly reducing depressive symptoms 24 h following a single intravenous (IV) infusion in a two-site randomized controlled trial (response rates to ketamine and midazolam were 64 and 28%, respectively; Murrough et al, 2013a). Randomized controlled trials have also found positive therapeutic effects of ketamine in bipolar depression (Zarate et al, 2012) and posttraumatic stress disorder (PTSD; Feder et al, 2014). Despite the potential of ketamine as a mechanistically novel therapeutic option for patients with TRD, important concerns regarding safety and toxicity remain (Green and Cote, 2009;Morgan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%